The co-occurrence of multidimensional loneliness with depression, social anxiety and paranoia in non-clinical young adults: A latent profile analysis - Chau, Anson Kai Chun; So, Suzanne Ho-wai; Sun, Xiaoqi; Zhu, Chen; Chiu, Chui-De; Chan, Raymond C. K.; Leung, Patrick W. L. (Frontiers in Psychiatry, 2022)
Introduction Loneliness is a negative experience arising from a mismatch between perceived and actual social relationships. Several dimensions of loneliness have been suggested, namely intimate, relational and collective loneliness. Loneliness has been linked to poorer mental health, with its co-occurrence with depression, social anxiety, and paranoia most widely reported. While expressions of these symptoms are heterogeneous across individuals in the non-clinical population, it remains unclear how these symptoms co-occur with one another and with various dimensions of loneliness. It is also of interest how trait factors such as core schemas about self/others may moderate these relationships between loneliness and co-occurring symptoms. Methods A demographically diverse sample of young adults was recruited from multiple sources. The validated sample consisted of 2,089 participants (68.4% female), who completed an online survey consisting of questionnaires assessing levels of multidimensional loneliness, depression, social anxiety, paranoia, core schemas, and demographic characteristics. Latent profile analysis (LPA) was used to identify distinct profiles of loneliness and the three symptoms. Positive and negative core schemas about self and others were modeled as predictors of these profiles. Results Five distinct profiles were identified. Profile 1 had low levels across all symptoms and dimensions of loneliness (n = 1,273, 60.9%). Profiles 2–5 were elevated on dimensions of loneliness, and were heightened in depression (n = 189, 9.0%), social anxiety (n = 206, 9.9%), paranoia (n = 198, 9.5%), and all symptoms (n = 223, 10.7%), respectively. Relative to Profile 1, the other four profiles scored higher on negative-self (adjusted ORs = 1.36–1.49, ps < 0.001) and negative-other schemas (adjusted ORs = 1.24–1.44, ps < 0.001), and lower on positive-self (adjusted ORs = 0.82–0.85, ps < 0.001) and positive-other schemas (adjusted ORs = 0.81–0.90, ps < 0.001). Conclusion More marked intimate, relational and collective loneliness were evident across profiles that had heightened depression, social anxiety and/or paranoia, suggesting that loneliness may serve as a general risk factor for these psychopathologies. Our findings shed light on the heterogeneity of the co-occurrence of loneliness and various mental health difficulties in non-clinical young adults. Core schemas are suggested to be putative psychological mechanisms underlying their co-occurrence and even development.